Rola sektora publicznego oraz prywatnego (for i non-profit) w zmniejszaniu różnic w edukacji przedszkolnej w Polsce AD 2013. Zmodyfikowany model mieszany czy prywatyzacja usług przedszkolnych? - Anna Ciepielewska-Kowalik (Problemy Wczesnej Edukacji)
The role of the public and the private for and non-profit sectors in decrease in inequalities in preschool education in Poland in 2013. Modified welfare mix or privatization of preschool services? The aim of this article is to investigate the role of the public and the private sector (for and nonprofit) in decrease in inequalities in preschool education in Poland in 2013. It is presented in relation to two different models of reforming early childhood education and care policy (ECEC), such as demand- driven privatization that coincides with the market model and supply-driven privatization that coincides with the democratic experimentalism. Taking into consideration territorial inequalities in preschool education in Poland, the author analyses what influence have both types of reforming ECEC policy on building the universal system of high quality preschools. Reforms in ECEC policy in 2007–2012, according to the most present changes in legal frameworks in preschool education is also examined in this article. Finally, different types of challenges in institutionalization of supplydriven privatization/democratic experimentalism and demand-driven privatization/market model of reforming ECEC policy is investigated. The article is based on Polish and foreign literature, as well as the analysis made by the author in her research project in 46 non-profit organisations running preschools in four voivodeships in Poland.